BIOGAS SEBAGAI ENERGI ALTERNATIF ANTARA MITOS dan FAKTA ILMIAH - Djoko Padmono (Jurnal Teknologi Lingkungan, 2007)
In the year of seventienth where the energy crisis struck the world, thecompeting person looked for the alternative to energy change the sourceof conventional energy (petroleum). One of the topics that it was hopedbecame alternative was BIOGAS from the process of the anaerobicfermentation of organic matter either agricultural or food industrial waste.Several parameters were studied to prove that anaerobic fermentationof the solid organic matter could become the BIOGAS as alternativeenergy replaced petroleum. Currently these all ideas were remains atthe myth completely.The reality from investigation of the technology degradation process /digestion of the organic matter by making use of this anaerobicfermentation system was only could be used as one of the wastetreatment as the solving problem of pollution of the environment, withresults of taking the form of BIOGAS that could be made use of assubstitution energy for the waste treatment it self. In other wordsanaerobic fermentation technology of the solid waste was one of thesolid waste treatments with minimal energy. Energy that was needed forwaste treatment process will be produced from himself to substituteenergy that was used from the network of the public (PLN). So as to behoped energy that usually is taken from the national net (PLN) for theprocessing of waste could be reduced, and was subtituted with energybiogas that was produced by him.